Comparison of Javanese medaka (Oryzias javanicus, Bleeker, 1854) and zebrafish (Danio rerio, Hamilton, 1822) as a model organism for neurotoxicological study - Ramlan, Nurul Farhana (2017)
Zebrafish is increasingly popular in neurotoxicology research due to their small size, low maintenance and efficient for high throughput testing. However, using nonnative species may raise concern on ecological aspect as accidental introduction of foreign species to our local aquatic environment could cause ecosystem instability. Therefore, the applicability of using Javanese medaka (JM) in the neurotoxicology and developmental neurotoxicology (DNT) research will be assessed by using zebrafish as a reference model. Assessment of the exploratory, anxiety and social behaviour were conducted by using open field test and aquatic light/dark plus maze. Biochemical assessment was conducted using Fourier Transform Infrared (FTIR) analysis. Without exposure to neurotoxicants, JM displayed less exploratory behaviour and showed no difference for anxiety and social behaviour as compared to the zebrafish. JM exhibited light preference while zebrafish showed dark preference. Exposure to 1% ethanol resulted a reduction in exploratory behaviour, induction in anxiety like behaviour and no alteration in the social behaviour of JM. Meanwhile, zebrafish showed a reduction in anxiety like behaviour and no alteration in exploratory and social behaviour. Treatment with 1.6 μg/L endosulfan resulted increment in exploratory behaviour, induction in anxiety like behaviour and decrement in social behaviour for both fishes. Exposure to 100 mg/L caffeine resulted anxiogenic response and decrement in the exploratory behaviour for both fishes. Alteration in social behaviour was only observed in the zebrafish. Both fishes showed alteration in biochemical profile after exposure to ethanol or endosulfan with regard to different macromolecules in the brain tissues. This study also found that, JM is inefficient for DNT research as they are laborious, time-consuming and not amenable for high throughput screening. More studies need to be conducted to further develop JM as an ideal model organism for neurotoxicology research.